2016
DOI: 10.1590/0103-6440201600666
|View full text |Cite
|
Sign up to set email alerts
|

Stress Distribution in Roots Restored with Fiber Posts and An Experimental Dentin Post: 3D-FEA

Abstract: The aim of this study was to compare the stress distribution in radicular dentin of a maxillary canine restored with either a glass fiber post, carbon fiber post or an experimental dentin post using finite element analysis (3D-FEA). Three 3D virtual models of a maxillary canine restored with a metal-ceramic crown and glass fiber post (GFP), carbon fiber post (CFP), and experimental dentin post (DP) were obtained based on micro-CT images. A total of 180 N was applied on the lingual surface of the incisal third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…While, in some studies, the 3D geometric tooth model is created in a virtual environment using the FEA method (1-3), there are many FEA studies based on µBT with the advancement of technology (21)(22)(23)(24). In finite element models made using the µBT technique, both bone and tooth tissue (enamel, dentin, and pulp) can be distinguished precisely (25).…”
Section: Discussionmentioning
confidence: 99%
“…While, in some studies, the 3D geometric tooth model is created in a virtual environment using the FEA method (1-3), there are many FEA studies based on µBT with the advancement of technology (21)(22)(23)(24). In finite element models made using the µBT technique, both bone and tooth tissue (enamel, dentin, and pulp) can be distinguished precisely (25).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that a dentin post enhances stability and adhesion, which reduces the risk of fracture of endodontically treated teeth. 3 The dentin post (Figure 5 a) can be prepared from extracted premolar or canine. After ensuring all the bio security standards the crown portion of the tooth selected for dentin post preparation was separated from the root using a diamond disk (Figure 5 b) and then the tooth was sectioned bucco-lingually along the long axis (Figure 5 c-e).…”
Section: Discussionmentioning
confidence: 99%
“…These posts are easy to use and show an elastic modulus similar to human dentin, which favors stress distribution along the root axis. 3 Ideally, the post material should have a physical property such as modulus of elasticity, compressive strength, and thermal expansion, as well as esthetics similar to those of dentin, and it should bond predictably to root dentin. However, the only material that can substantiate all these properties can be none other than dentin itself.…”
Section: Introductionmentioning
confidence: 99%
“…performed a finite elemental analysis study to compare stress distribution in teeth restored with fiber post, dentin post, and concluded that both the posts presented a similar biomechanical performance. [ 9 ] The polymer matrix in the prefabricated fiber posts is highly cross-linked and, therefore, less reactive. This makes it difficult for these posts to bond to resin luting agents.…”
Section: Discussionmentioning
confidence: 99%